2020
DOI: 10.1186/s12889-019-8067-4
|View full text |Cite
|
Sign up to set email alerts
|

Workers’ physical activity data contribute to estimating maximal oxygen consumption: a questionnaire study to concurrently assess workers’ sedentary behavior and cardiorespiratory fitness

Abstract: Background: Sedentary behavior (SB) and cardiorespiratory fitness (CRF) are important issues in occupational health. Developing a questionnaire to concurrently assess workers' SB and CRF could fundamentally improve epidemiological research. The Worker's Living Activity-time Questionnaire (WLAQ) was developed previously to assess workers' sitting time. WLAQ can be modified to evaluate workers' CRF if additional physical activity (PA) data such as PA frequency, duration, and intensity are collected. Methods: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
5
31
0
Order By: Relevance
“…Many previous studies of . VO 2max prediction have also found that PBF is a better predictor than BMI [2,40,41]. Therefore, when financial conditions permit, people can consider adopting the PBF models to evaluate their .…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies of . VO 2max prediction have also found that PBF is a better predictor than BMI [2,40,41]. Therefore, when financial conditions permit, people can consider adopting the PBF models to evaluate their .…”
Section: Discussionmentioning
confidence: 99%
“…The authors found strong correlations, R = 0.85 (SEE 3.11) and R = 0.84 (SEE 4.15), compared to maximal cycle ergometer testing [ 23 , 24 ]. More recently, Matsuo et al developed an eCRF PAS-based equation compared to maximal treadmill test in working Japanese adults ( n = 198) and found a strong correlation ( r = 0.77) [ 25 ]. As expected, the PAS model correlations are higher than our eCRF model without PAS; beyond genetics, PAS is an essential variable for modifying CRF [ 2 , 4 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the PAS model correlations are higher than our eCRF model without PAS; beyond genetics, PAS is an essential variable for modifying CRF [ 2 , 4 , 11 ]. Though these eCRF PAS-based correlations are higher, access to specific PAS data from existing EMR datasets is not likely to have been recorded in EMRs [ 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in which the first author was unsure whether to be included were discussed and determined with the last author. A study was eligible for our meta-analysis if it met the following criteria: (1) experimental studies assessing PAV as a dependent variable; (2) PAV was a target of the intervention; (3) studies whose goal was to increase lifestyle or recreational PA, not for competitive sports (Caspersen et al, 1985 ; Vanhees et al, 2005 ); (4) sufficient data to calculate the effect sizes (Hedges' g) of PAVs and PA; (5) participants were healthy individuals (not a clinically defined population and not pregnant). Furthermore, we intentionally chose a minimum duration of PA of 10 min, given that 10 min is the recommended minimum duration of exercise to elicit health benefits (Edwards and Loprinzi, 2019 ).…”
Section: Methodsmentioning
confidence: 99%